Oxygen Migration in Dense Spark Plasma Sintered Aluminum‐Doped Neodymium Silicate Apatite Electrolytes. Issue 11 (2nd August 2013) - An, Tao; Baikie, Tom; Herrin, Jason; Brink, Frank; Felix Shin, J.; Slater, Peter R.; Li, Sean; White, Tim J.
Abstract : Neodymium silicate apatites are promising intermediate temperature (500°C–700°C) electrolytes for solid oxide fuel cells. The introduction of Al promotes isotropic percolation of O 2−, and at low levels (0.83–2.0 wt% Al) enhances bulk conductivity. To better understand the effect of Al‐doping on intrinsic conductivity, and the impact of grain boundaries on the transport, dense Nd9.33+ x /3 Al x Si6− x O26 (0 ≤  x  ≤ 2) pellets were prepared by spark plasma sintering. Phase purity of the products was established by powder X‐ray diffraction and the microstructure examined by scanning electron microscopy. The ionic conductivity measured by AC impedance spectroscopy for the spark plasma sintered ceramics were compared with transport in single crystals of similar composition. Intermediate Al‐doping (0.5 ≤  x  ≤ 1.5) delivered superior overall conductivity for both the polycrystalline and single crystal specimens.